2015
DOI: 10.1002/cne.23842
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of social and physical environmental enrichment on brain plasticity, cognition, and ultrasonic communication in rats

Abstract: Environmental enrichment (EE) exerts beneficial effects on brain plasticity, cognition, and anxiety/depression, leading to a brain that can counteract deficits underlying various brain disorders. Because the complexity of the EE commonly used makes it difficult to identify causal aspects, we examined possible factors using a 2 × 2 design with social EE (two vs. six rats) and physical EE (physically enriched vs. nonenriched). For the first time, we demonstrate that social and physical EE have differential effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
107
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 108 publications
(253 reference statements)
7
107
1
3
Order By: Relevance
“…Finally, USV emission by the subject rat in response to playback of 50-kHz USVs can be determined (Avisoft Bioacoustics). By this means, it has been consistently shown that 50-kHz USVs lead to social approach behavior in juvenile and adult male rats (Wöhr and Schwarting, 2007, 2009, 2013Brenes et al, 2016;Seffer et al, 2015) as well as in female rats (Willadsen et al, 2014; Fig. 8.35.2), supporting the notion that they serve an affiliative function as social contact calls.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Finally, USV emission by the subject rat in response to playback of 50-kHz USVs can be determined (Avisoft Bioacoustics). By this means, it has been consistently shown that 50-kHz USVs lead to social approach behavior in juvenile and adult male rats (Wöhr and Schwarting, 2007, 2009, 2013Brenes et al, 2016;Seffer et al, 2015) as well as in female rats (Willadsen et al, 2014; Fig. 8.35.2), supporting the notion that they serve an affiliative function as social contact calls.…”
mentioning
confidence: 80%
“…No social deficits were seen when long-term social isolation was implemented after the rough-and-tumble play period. In the second study (Brenes et al, 2016), the effects of social versus physical environmental enrichment on social approach behavior in response to playback of 50-kHz USVs were compared. While rats housed in groups of two displayed social approach behavior, more prominent approach behavior was seen in rats housed in groups of six.…”
Section: Housing Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Newberry, 1995;Young, 2003). EE exerts beneficial effects on brain, behavior and cognition, for instance by affecting endocrinologic, immunologic, and neuroplastic parameters (Buscherta et al, 2016;Brenes et al, 2016). EE applications are often discussed within the context of welfare of animals hosted in cages (Wolfie, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, our understanding of the effect of EE on connectivity between brain regions is rudimentary. Studies have shown that EE can influence brain plasticity in the hippocampus [19] , amygdala [20], and prefrontal cortex [21] . However, these studies have failed to provide information about neuronal oscillations which have functional relevance to the behavior of animals.…”
Section: Introductionmentioning
confidence: 99%